(untitled) (London Journal of Research In Science: Natural and Formal, 2023)
The coupling coordination degree (CCD) is considered to be an important yardstick for guiding practice toward sustainable development. It helps quantitatively investigate the interactions between two or more subsystems within a complex system. However, the existing CCD models have inherent shortcomings. Currently, no consensus has been reached on CCD models. In line with this background, this research proposes a new CCD model from the perspective of the cosine of the high-dimensional spatial angle and develops a novel Excel© tool named Ex-CCD. Taking the coupling coordination analysis between economic-social development, resource consumption, and environmental pollution in China during 2000–2016 as an example, a case demonstration is conducted, and the results show that the model proposed in this research can more accurately describe the coupling coordination state of a system. This new model provides a significant theoretical and practical basis as well as a novel perspective for further coupling coordination research.